Biosynthesis of Zinc Oxide Nanoparticles from Soil Fungi and their Characterization by Using Analytical Methods - Bottangada, Amitha Ganapathy; Subhakar, Akarsh; Veeranna, Sowmya Hirakannavar; Basaiah, Thippeswamy (Asian Journal of Biological and Life Sciences)
Aims: The main aim of the study is to synthesize the zinc oxide nanoparticles from fungal isolates of soil and characterize the physicochemical properties of synthesized ZnO NPs for agricultural purposes. Materials and Methods: The soil samples have been collected, isolated, and examined for the solubilization of zinc. The promising isolate was molecular characterized and deposited in NCBI GenBank. This isolate was then utilized to synthesize and characterize ZnO nanoparticles. The synthesized ZnO NPs were characterized using UV-vis DRS, UV-vis spec, DLS, XRD, FT-IR, and SEM-EDAX for confirmation and quantification. Results: In the 14 fungal isolates, Aspergillus fumigatus (Db5) has shown the highest zinc solubilization index of 2.75mm. The fungal culture filtrate displayed an absorption peak at 315 nm in UV-visible spectrum analysis whereas, in UV-vis DRS, it showed 330nm with a band gap found to be ~3.1 eV, which indicated the presence of zinc oxide. The synthesized ZnO-NPs measure 27.35 nm in particle size and have a zeta potential of -2.35 mV. The average size of the ZnO NPs was found to be 23nm through XRD. The functional hydroxyl (O-H) group of the ZnO NP showed an intense band near 3447.16 cm-1 through FT-IR analysis. In SEM studies, the morphology of ZnO NPs was found to be irregular, spherical, and granule-like structures. Conclusion: All the studies indicate that the fungal isolate Aspergillus fumigatus (Db5) can synthesize ZnO NPs which can be further tested for crop protection and production as an eco-friendly approach.
Keywords: Analytical techniques; Aspergillus fumigatus; Biosynthesis; eco-friendly; Zinc oxide nanoparticles